Cardiac failure following inadvertent administration of high-dose epinephrine subcutaneously - Tran, Kim A.; Fraser, Douglas D.; Hawrylyshyn, Krista; Norozi, Kambiz (Journal of Pediatric Intensive Care, 2012)
Our aim is to report the consequences of epinephrine toxicity leading to cardiac failure in a child and the successful management with dopamine and milrinone. A previously healthy 13-year-old girl undergoing a left tympanomastoidectomy was inadvertently administered 10 mL of 1:1000 epinephrine subcutaneously (0.175 mg/kg) on the left post auricular region in lieu of lidocaine. She developed sudden supraventricular tachycardia, hypertension and flash pulmonary edema. She was initially treated with propofol, nitrogycerin and increased peak end-expiratory pressure. Within 4 h, she remained tachycardic, but was hypotensive with an increased central venous pressure. Electrocardiogram and echocardiogram investigations showed ST changes indicative of myocardial ischemia and globally reduced function, respectively. Dopamine infusion was administered, together with milrinone, resulting in a gradual improvement of cardiac function within 3 days. She was transitioned to enalapril and discharged home. This case highlights the clinical features of high dose epinephrine toxicity secondary to iatrogenic subcutaneous overdose followed by hypotension and pulmonary edema as a possible late effect of epinephrine and the successful management of secondary cardiac failure with administration of dopamine, milrinone and enalapril.
Keywords: Epinephrine; drug toxicity; dopamine; milrinone; myocardial ischemia; pulmonary edema